Depletion of O6-alkylguanine-DNA alkyltransferase correlates with potentiation of temozolomide and CCNU toxicity in human tumour cells. - Baer, J. C. (Nature Publishing Group, 1993)
Temozolomide (8-carbamoyl-3-methylimidazo[5,1-d]-1,2,3,5-tetrazin-4-(3H)-one) has shown promising activity in Phase I trials against some brain (glioma) and skin (melanoma, mycosis fungoides) cancers. Temozolomide and lomustine (CCNU) showed parallel toxicity in seven human tumour cell lines and this generally correlated (correlation coefficients 0.87 and 0.92 respectively) with the level of expression of the DNA repair protein O6-alkylguanine-DNA alkyltransferase (ATase, EC 2.1.1.63). Pretreating cells with the ATase inhibitor, O6-benzylguanine (BG), potentiated cytotoxicity to a similar degree with both drugs, but did not sensitise a cell line (ZR-75-1) expressing very low levels of this protein. When BG pretreatment was combined with repeat doses of temozolomide a dramatic potentiation (300 fold) was seen in MAWI cells, which express high levels of ATase, but not in a cell line (U373) expressing lower levels of ATase. [14C]-labelled temozolomide uptake was similar in sensitive and resistant lines. Human ATase-cDNA transfected xeroderma pigmentosum (XP) fibroblasts were more resistant than XP control cells to temozolomide and the related chloroethylating agent mitozolomide and although BG completely suppressed ATase activity in these cells, resistance was still greater than in control cells.